'Offering something back to society?' Learning disability, ethnicity and sporting legacy: hosting the Special Olympics GB Summer Games in Leicester, 2009. (30th May 2013) - Williams, John; Carter, Neil
<x xml:space="preserve">Abstract</x> Accessible summary This article is about research on hosting major sporting events involving people with learning disabilities. It focuses on the Special Olympics Great Britain National Summer Games, which were held in Leicester in July 2009. The 2009 Summer Games raised significant legacy issues concerning ethnicity, both for the hosts (the city of Leicester) and the governing body, Special Olympics Great Britain. The event also provided important insights into wider attitudes towards people with learning disabilities held by the general public. Summary In 2009 the city of Leicester hosted the Special Olympics Great Britain National Summer Games. Around 2500 athletes with learning disabilities competed in 21 sports. This article argues that this sporting mega‐event had important potential legacy consequences for the hosts, the governing body – Special Olympics Great Britain (SOGB) – and also for wider attitudes towards people with learning disabilities. We are mainly concerned here with questions of ethnicity around Special Olympics Great Britain (SOGB) and the specific motivations for staging this event in the East Midlands. We argue that the hosts mobilised a set of quite unusual rhetorics and legacy aims in its appeal to local citizens, and that SOGB favoured Leicester because of the organisation's urgent need to modernise in terms of its urban reach, ethnicity and age profiles. We end by briefly assessing the evidence that SOGB achieved some of its goals and the extent to which the Leicester public embraced Special Olympics and athletes with learning disabilities.